Cooperative Electronic Structure Modulator of Fe Single‐Atom Electrocatalyst for High Energy and Long Cycle Li–S Pouch Cell. Issue 10 (10th January 2023) - Lim, Won‐Gwang; Park, Cheol‐Young; Jung, Hyeonjung; Kim, Seoa; Kang, Seok Hun; Lee, Young‐Gi; Jeong, Yo Chan; Yang, Seung Bo; Sohn, Kwonnam; Han, Jeong Woo; Lee, Jinwoo
Abstract: High‐energy and long cycle lithium–sulfur (Li–S) pouch cells are limited by the insufficient capacities and stabilities of their cathodes under practical electrolyte/sulfur (E/S), electrolyte/capacity (E/C), and negative/positive (N/P) ratios. Herein, an advanced cathode comprising highly active Fe single‐atom catalysts (SACs) is reported to form 320.2 W h kg −1 multistacked Li–S pouch cells with total capacity of ≈1 A h level, satisfying low E/S (3.0), E/C (2.8), and N/P (2.3) ratios and high sulfur loadings (8.4 mg cm −2 ). The high‐activity Fe SAC is designed by manipulating its local environments using electron‐exchangeable binding (EEB) sites. Introducing EEB sites comprising two different types of S species, namely, thiophene‐like‐S (–S) and oxidized‐S (–SO2 ), adjacent to Fe SACs promotes the kinetics of the Li2 S redox reaction by providing additional binding sites and modulating the Fe d‐orbital levels via electron exchange with Fe. The –S donates the electrons to the Fe SACs, whereas –SO2 withdraws electrons from the Fe SACs. Thus, the Fe d‐orbital energy level can be modulated by the different –SO2 /–S ratios of the EEB site, controlling the electron donating/withdrawing characteristics. This desirable electrocatalysis is maximized by the intimate contact of the Fe SACs with the S species, which are confined together in porous carbon. Abstract : The introduction of electron exchangeable binding sites comprising thiophene S and oxidized S, adjacent to Fe single atom electrocatalysts, improves Li2 S redox kinetics by modulating d‐orbital level of Fe single atom via electron exchange. These specially designed electrocatalysts enable realization of a 1 A h level Li–S pouch cell with high gravimetric energy density and long cycle stability.